(untitled) (Fiep Bulletin - online, 2014)
This is a descriptive study aimed at identifying the prevalence of venous ulcers (VU), and the sociodemographic and health characteristics of VU patients treated in the Family Health Units (FHUs). The target population was composed of 74 VU patients treated by Family Health Program (FHP) teams in the 31 FHUs. The study was approved by the Ethics Committee of the Universidade Federal do Rio Grande do Norte (protocol no. 55/05). Data collection, using a structured interview, was performed in the patients’ residence and in the FHUs. The data were organized in an Excel column chart and transferred to SPSS software, version 14.0 for descriptive analysis using 2x2 contingency tables and inferential statistics (Chi-square-÷2, Pearson’s correlation and p-value <0.05). The prevalence of VU in the target population (0.36/1000) was greater than that of the population enrolled in the FHP (0.25/1000). We detected a higher prevalence (2.22/1000) in the = 60-year age group (2.98/1000 in women, and 1.3/1000 in men, p-value=0.008). The sociodemographic and health characteristics of the VU patients showed a predominance of women (74.5%), individuals = 60 years of age (67.6%), elementary schooling (74.3%), family income = US350.00 (68.9%), retired individuals (90.5%), the standing position (23.0%), insufficient sleep (59.5%), the presence of CVI (100.0%), hypertension (44.6%), and diabetes (25.7%). We conclude that the prevalence found is in accordance with national and international studies and that a majority of VU patients are women, elderly, have low socioeconomic conditions, and suffer from associated chronic diseases.